Mechanical Properties of Membranes of Poly(L-co-DL-lactic acid) with Poly(caprolactone triol) and Study In Vivo - Marcia Adriana Tomaz Duarte; Adriana Cristina Motta; Eliana Aparecida de Rezende Duek (International Journal of Polymer Science)
There is increasing interest in aliphatic polyesters from lactones and lactides because of their biodegradability and biocompatibility. Among these compounds, poly(lactide), and poly(glycolide), poly(ε-caprolactone) and their copolymers are especially interesting because of their potential applications as biomedical materials. The aim of this study was to examine the properties of membranes of poly(L-co-D,L lactic acid) (PLDLA) with poly(caprolactone triol) (PCL-T) obtained by solvent evaporation. The blends were characterized by differential scanning calorimetry, dynamic mechanical analysis, Fourier transform infrared spectroscopy, and tensile strength tests. Based on the results of in vitro studies, PLDLA/PCL-T blends of 100/0 and 90/10 were implanted in subcutaneous tissue of Wistar rats for 1, 3, 7, 15, and 60 days to evaluate their biocompatibility. Histological analysis indicated that, although PCL-T-containing membranes caused a more prominent inflammatory reaction in the initial time intervals, by 60 days after implantation, the material was surrounded by dense, organized collagen with almost no inflammatory infiltrate.